A Comparative study on Traditional Transport System and Intelligent Transport System - Khan, Irfan Ali; Khan, Rizwan; Shukla, Ravi Shankar (MATRIX Academic International Online Journal Of Engineering And Technology, 2013)
This paper presents intelligent transport system for communication in city environment. In this intelligent transport system, we provide information about bus’s location and number of students, faculty present in the bus. The intelligent transport system follows the concept of VANET and uses the routing protocols. VANET plays a very important role in ADHOC networking. With the help of VANET, the intelligent transport can exchange information to-and-from another buses and also exchange the information to college. With the help of the VANET, we can track the bus location and all other information related to the bus.